Perencanaan Pembangunan Kawasan Ekowisata Taman Buah Jeruk Kabupaten Malang (Studi di Dinas Pariwisata dan Kebudayaan Kabupaten Malang) - Wiyanti, Titik (Jurnal Ilmiah Administrasi Publik, 2021)
This research aims to analyse the development planning of the area of the Jeru Fruit garden in Malang District (study at the Tourism and Culture Office of Malang District). Researchers analyzed development planning using 6 (six) components, namely The decision to adopt planning, collect and analyse data, identyfing alternatives course of action, plan and project appraisal, implement, and monitoring and evaluation. The type of research used is descriptive research with a qualitative approach. The results of the research show that development planning is seen from 6 (six) components, that the implementation of the ecotourism area of Jeru Fruit Park in Malang district has been more than 4 (four) years but in fact there are still many activities have not been carried out optimally, such as the many physical results of development that has been completed but still not be utilized because of the lack of management certainty that can generate income as a source of Original Local Government Revenue.